REVITALISASI KEARIFAN LOKAL: PENGEMBANGAN WADAH KERUKUNAN DAN KETAHANAN MASYARAKAT LOKAL DI KECAMATAN DONGGO KABUPATEN BIMA PROVINSI NTB - Haidlor Ali Ahmad (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The purpose of this research are determining and describing the harmony situation in Dongo, Bima, Nusa Tenggara Barat; identifying and describing the conflict potential and its attempts to resolve it; knowing and describing the way people use local wisdom in order to harmony keeping, anticipating and resolving conflicts. The expected results of this research are: firstly, as an input to policy makers in maintaining harmony and increasement of community roles on harmony keeping through local wisdom revitalization. This research is part of the Participatory Action Researche (PAR). The main source of data in this study interviews, observation, documentation / literature review and Focus Group Discussion.